Optimization of Phellinus hartigii extracts: Biological activities, and phenolic content analysis - Orhan Ünal; Ayşenur Gürgen; Tetiana Krupodorova; Mustafa Sevindik; Şanlı Kabaktepe; Ilgaz Akata (BMC Complementary Medicine and Therapies)
Abstract Background Medicinal mushrooms are sources of natural substances with diverse biological functions. The study evaluated the biological activity of Phellinus hartigii (Allesch. & Schnabl) Pat. and optimized extraction conditions to the maximize its bioactive potential. Methods Extraction was performed using a Soxhlet apparatus under varying conditions: temperatures (30, 50, and 70 °C), durations (1, 5.5, and 10 h), and ethanol/water ratios (0%, 50%, and 100%). Total antioxidant status (TAS) was analyzed across 17 experiments, and the optimal conditions were identified using response surface methodology (RSM). Extracts from optimal conditions were further analyzed for antioxidant capacity (Rel assay kits, DPPH, FRAP), anticholinesterase activity (acetyl- and butyrylcholinesterase inhibition), antiproliferative activity (A549 lung cancer cell line), total phenolic content (Folin-Ciocalteu method), and phenolic compound profile (LC–MS/MS). Results Optimal extraction conditions were determined to be 48.22 ˚C, 9.04 h, and an ethanol/water ratio of 52.22%. The extract exhibited significant antiproliferative effects against the A549 lung cancer cells, with activity increasing in a concentration-dependent manner. The inhibition values (IC50) of acetylcholinesterase and butyrylcholinesterase were 21.29 ± 0.41 and 35.51 ± 0.53 μg/mL, respectively. The TPC (total phenolic content) value of the optimized extract was determined as 88.21 ± 1.50 mg/g, FRAP value as 137.81 ± 1.72 mg/g, DPPH value as 106.07 ± 2.44 mg/g, TOS (total oxidant status) value as 9.27 ± 0.06 µmol/L, TAS value as 4.98 ± 0.03 mmol/L and OSI (oxidative stress index) value as 0.19 ± 0.002. LC–MS/MS analysis identified nine phenolic compounds, with gallic acid and catechin hydrate as the most abundant. Conclusions The extract of P. hartigii obtained under optimal conditions demonstrated substantial antioxidant, anticholinesterase, and antiproliferative activities, highlighting its therapeutic potential.